2022
DOI: 10.47654/v26y2022i1p31-68
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships among Authentic Leadership, Social Exchange Relationships, and Trust in Organizations during COVID-19 Pandemic

Abstract: Trust is essential for organizations' cooperative relationships during COVID-19. Authentic leadership and social exchange relationships are required to increase trust during a crisis. However, leader behaviors during COVID-19 have effects on the relationships among authentic leadership, social exchange relationships, and trust in organizations to understand their effects. The moderating effects of leader behaviors during COVID-19 on the relationships among authentic leadership, social exchange relationships, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…An overarching theme across the three dimensions predicting organizational support is that employees develop perceptions about their organization by way of social exchange relationships. Over time, those exchange relationships strengthen or weaken an employee's perceived organizational support (Chen and Sriphon, 2022). While research is rife with examples of predictors that serve to strengthen perceived organizational support, far less attention has been paid to the negative events that may weaken an employee's perceived organizational support.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…An overarching theme across the three dimensions predicting organizational support is that employees develop perceptions about their organization by way of social exchange relationships. Over time, those exchange relationships strengthen or weaken an employee's perceived organizational support (Chen and Sriphon, 2022). While research is rife with examples of predictors that serve to strengthen perceived organizational support, far less attention has been paid to the negative events that may weaken an employee's perceived organizational support.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…A study conducted by Chen and Sriphon (2022) indicated that authentic leadership was linked positively to both social exchange relationships and trust. Furthermore, an authentic leadership style can promote a healthy and supportive work setting characterized by sound relationships and trust among team members, follower trust in their leaders ( Asad et al, 2021 ), and in their organization ( Miniotaite and Buciuniene, 2013 ; Alkaabi, 2018 ; Kleynhans et al, 2021a ).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Emerging research from Taiwan suggests that authentic leadership positively affects social exchange relationships and trust, whereas social exchange relationships positively affect trust after COVID-19 ( Chen and Sriphon, 2022 ). Moreover, they found that a social exchange relationship had a mediating effect between authentic leadership and trust ( Chen and Sriphon, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging research from Taiwan suggests that authentic leadership positively affects social exchange relationships and trust, whereas social exchange relationships positively affect trust after COVID-19 ( Chen and Sriphon, 2022 ). Moreover, they found that a social exchange relationship had a mediating effect between authentic leadership and trust ( Chen and Sriphon, 2022 ). In the same vein, a study of crisis leadership in Norwegian school principals corroborates the significance of attending to social exchange relationships and emotion management processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation